The Brussels swimming EMG project - Clarys, J. P. (Swimming Science V, 1988)
This project started in 1970, in a Dutch marine ship model test station (Figure 1) as a result of the study of fundamental and applied hydrodynamics of living human body shapes. This test station allowed for the measurement of passive drag in different positions and of active (swimming) drag. It was found contrary to the general belief that drag in a prone position 60 cm under the water surface was greater than at the water surface or swimming level and that active drag while swimming the front crawl at different velocities reached one and a half to twice the drag values of any passive drag condition (see Figure 2; Oarys, 1979; Oarys & Jiskoot, 1974; 1975; Oarys, Jiskoot, & Lewillie, 1973; Jiskoot & Oarys, 1975). The combination of physics (hydrodynamics) and electrophysiology (EMG) may appear bizarre at first, but in reality these disciplines are highly complementary when ergonomic aspects of aquatics are considered. Hydrodynamics is concerned with drag and propulsion phenomena but because drag equals propulsion at constant velocity, propulsion is usually calculated from a drag-velocity relationship. On the other hand, EMG deals with the direct recording of electrical potentials of the active muscles. In the case of swimming movements, it gives an expression of the dynamic involvement of specific muscles in the propulsion of the body through the water.